Family Link: Inovasi Edukasi Digital bagi Orang Tua dan Guru dalam Mengawasi Aktivitas Online Anak: Family Link: Digital Education Innovation for Parents and Teachers in Monitoring Children's Online Activities - Yuniarti Lestari; Tresna Yudha Prawira; Umar Ghoni; Nur Wahyu Hidayat; Hidayatur Rakhmawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The increase in internet access among early childhood in rural areas is often not accompanied by adequate parental supervision skills, thereby increasing the risk of gadget addiction and exposure to negative content. This community service program aims to improve the digital literacy of parents and teachers at RA Al Manshur, Bangbayang Village, by optimizing parental mediation. The implementation method includes socialization on the urgency of digital supervision, technical training on using the Google Family Link application, and direct practical simulations guided by a team of lecturers and students. Participants consisted of 27 parents and 3 teachers. Evaluation results showed an average increase in participants' understanding of 35%, with 85% feeling more confident in monitoring their children's online activities. The program has reached 60% completion and has proven effective in equipping parents with the tools to create a safe, healthy digital environment for children.